Wastewater Treatment Plant Design Software Development with Borland Delphi 7.0 - Arumdhati, Fadhila Sanaz; Nizam, Nizam (2011)
Lack of standardized wastewater treatment facility caused pollution problems by untreated wastewater. Wastewater treatment plant design is a complex process and full of meticulous details, this makes the design process difficult and exhaustive to be done. Computer-aided design is an alternative to solving the problem. A software for wastewater treatment plant design had been developed by the authors that can assist the design of wastewater treatment plant. The software incorporates 32 tables, 10 graphs, and 203 formulas which can be used in the design of wastewater treatment plant. The software had been tested to a number of undergraduate and graduate students, mostly satisfy with the user interface and results.